Le drageonnage pour la regénération d’espèces médicinales en Afrique tropicale : cas du Spathodea campanulata en Ouganda - Meunier Quentin; Ronald Bellefontaine; Jean-Marc Boffa (VertigO)
In Africa since more than one half century, deciduous forests and open woodlands are seriously harvested for their commercial value and/or for medicinal purposes, and also for the continual research of new lands for agriculture or livestock. Many woody species are disappearing in agricultural and forest systems of Equatorial and Tropical Africa, due to harvesting practices and low natural regeneration. In Uganda, and particularly in the south-western habited zones of the country, the situation is getting worse very rapidly and it is urgent to regenerate these ecosystems before the socio-economical condition deteriorates too much. Vegetative propagation techniques at low cost, such as the root sucker induction method, can provide alternatives for a sustainable regeneration of species required by local populations. Observations were made in Uganda on Spathodea campanulata, for which root systems have been damaged by human activities. We observed physiological reactions on stressed roots. The total severance of a root always induced neo-formation of one or several root suckers on the distal part of the root section (root disconnected from the mother tree). Proximal parts of the roots stabilized or created new roots. Superficial or deep injuries on earthed or unearthed roots did not produce any roots or root suckers. In such cases, we observed the formation of callosity covering the injury. Sustainable development depends necessary on the regeneration at low cost of the woody resources. These poor populations, who don’t even have the essential, need these resources in order to combat disease and increase the incomes by the commercialisation of non woody forest products. This study confirms that artificial induction may lead to root sucker development and thus control the propagation of the species. Through similar case studies and species-based observations, such vegetative propagation methods can be replicated and transferred to threatened woody species in Tropical Africa.